Analysis of the Nature of Science in the â€œMerdekaâ€ Curriculum and Elementary Science Books and Their Comparison Between Countries - Ika Rosmiati; Nurul Saadah Agustina; Yusup Maulana; Ari Widodo (Postgraduate, University of Mataram, 2022)
The nature of science is essential to be conveyed in the curriculum and student books because it becomes a reference in the learning process to adequately achieve learning objectives. This study aims to describe aspects of the nature of science in the